Material Processes in BBC’s Articles on Plastic Pollution - Alwasilah, Autumn Windy; Sujatna, Eva Tuckyta Sari; Indrayani, Lia Maulia (JOMANTARA, 2024)
Like many other pressing problems in today's society, plastic pollution is being investigated by linguists under the subcategory of ecolinguistics. In this context, the present study tries to identify the material process in BBC's selected articles on plastic pollution. In particular, by using the Systemic Functional Linguistics (SFL) by Halliday & Matthiessen (2014), the study qualitatively analyzes the way how material processes in SFL indicate something that has been done physically between two entities in a clause. This research explains verbs as material processes in clauses and the function of their appearance in BBC’s selected articles based on transitivity analysis as part of SFL and categorizes them as creative or transformative processes. From this research, it can be seen that the material process is very useful in writing texts, especially in defining a process, whether it is creative, or transformative. From the analysis, the actor tends to change of some aspects of the existing things, rather than creating the new ones by the process. Keywords: BBC, ecolinguistics, material process, plastic pollution, systemic functional linguistics